Using GIS to develop a mobile communications network for disaster-damaged areas - Kawamura, Y.; Dewan, Ashraf; Veenendaal, Bert; Hayashi, M.; Shibuya, T.; Kitahara, I.; Nobuhara, H.; Ishii, K. (Taylor & Francis, 2013)
Communications network damage resulting from a large disaster causes difficulties in the ability to rapidly understand the current situation and thus make appropriate decisions towards mitigating problems, such as where to send and dispense emergency supplies. The research outlined in this paper focuses on the rapid construction of a network after a disaster occurs. This study suggests ZigBee and geographic information systems (GIS) technologies to resolve these problems and provide an effective communication system. The experimental results of the ZigBee network system are presented, examples are provided of the mapping and analysis undertaken using GIS for the disaster-stricken area of Tsukuba City, Japan, and the communications node arrangements are determined for this region. These results demonstrate the effectiveness of establishing such a communications system for supporting efforts to relieve disaster-damaged areas.